2022
DOI: 10.3390/biomedicines10071639
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Vitiligo Immunopathogenesis

Abstract: Vitiligo is an acquired immune-mediated disorder of pigmentation clinically characterized by well-defined depigmented or chalk-white macules and patches on the skin. The prevalence of vitiligo varies by geographical area, affecting 0.5% to 2% of the population. The disease imposes a significant psychological burden due to its major impact on patients’ social and emotional aspects of life. Given its autoimmune background, vitiligo is frequently associated with other autoimmune diseases or immune-mediated diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 162 publications
2
18
0
Order By: Relevance
“…showed that RDV suppresses mitochondrial respiration, induces mitochondrial fragmentation, and decreases the redox potential resulting in cardiotoxicity 17 . As mentioned before, mitochondrial dysfunction decreases the resistance of melanocytes to oxidative stress and predisposes patients to vitiligo 5 . Therefore, RDV administration might have played a role in vitiligo manifestation in our patient.…”
Section: Discussionsupporting
confidence: 57%
“…showed that RDV suppresses mitochondrial respiration, induces mitochondrial fragmentation, and decreases the redox potential resulting in cardiotoxicity 17 . As mentioned before, mitochondrial dysfunction decreases the resistance of melanocytes to oxidative stress and predisposes patients to vitiligo 5 . Therefore, RDV administration might have played a role in vitiligo manifestation in our patient.…”
Section: Discussionsupporting
confidence: 57%
“…Numerous pathomechanisms have been proposed to elucidate melanocyte destruction in vitiligo, including oxidative stress, innate and adaptive immune responses, inflammasome activation, genetic susceptibility, and melanocyte detachment mechanisms 17–19 . While a precise cause is still subject to debate, most evidence supports a central role of the interferon gamma (IFN‐γ)–CXCR3‐CXCL9/10 axis in inducing cytotoxic CD8+ T cell–targeted destruction of melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ, which activates JAK/STAT pathway and causes keratinocytes to produce the chemokines CXCL9 and CXCL10. 6 Fig. 4: Mediators in vitiligo Tumor necrosis factor-alpha (TNF-α) is one of the major cytokines implicated in the pathogenesis of vitiligo.…”
Section: Pathogenesismentioning
confidence: 99%